2011
DOI: 10.1093/nar/gkr669
|View full text |Cite
|
Sign up to set email alerts
|

Activity, specificity and structure of I-Bth0305I: a representative of a new homing endonuclease family

Abstract: Novel family of putative homing endonuclease genes was recently discovered during analyses of metagenomic and genomic sequence data. One such protein is encoded within a group I intron that resides in the recA gene of the Bacillus thuringiensis 0305ϕ8–36 bacteriophage. Named I-Bth0305I, the endonuclease cleaves a DNA target in the uninterrupted recA gene at a position immediately adjacent to the intron insertion site. The enzyme displays a multidomain, homodimeric architecture and footprints a DNA region of ∼6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…The CRISPR-associated protein Cas9 that belongs to the type II CRISPR/ Cas system has attracted much attention due to its potential use in genomic engineering. Cas9 contains one HNH motif and three RuvC-like motifs, homologous to HNH and RuvC endonucleases, respectively (Supplementary information, Figure S1) [4][5][6][7][8]. Recent studies showed that Cas9 displayed strong DNA cleavage activity in bacteria and in test tubes.…”
Section: Dear Editormentioning
confidence: 99%
“…The CRISPR-associated protein Cas9 that belongs to the type II CRISPR/ Cas system has attracted much attention due to its potential use in genomic engineering. Cas9 contains one HNH motif and three RuvC-like motifs, homologous to HNH and RuvC endonucleases, respectively (Supplementary information, Figure S1) [4][5][6][7][8]. Recent studies showed that Cas9 displayed strong DNA cleavage activity in bacteria and in test tubes.…”
Section: Dear Editormentioning
confidence: 99%
“…Studies on P-loop NTPases showed that one key active site residue, namely the arginine finger, is not conserved and has independently evolved on multiple occasions, either within the core fold, or in linked domains, or in separate proteins [53]. More drastic alterations of active sites are seen in DNases of the restriction endonuclease fold—the Vsr (very short patch DNA repair)-like endonucleases have undergone a reconfiguration of the ancestral active site via loss of two key residues and acquisition of two new ones from entirely different locations in their structure [47,54-56]. Despite this the spatial position of the active site pocket and their catalytic activity remains comparable to the ancestral versions.…”
Section: Reorganization Of Active Site Residues While Retaining Ancesmentioning
confidence: 99%
“…A strand-specific nicking variant has also been isolated from I-SceI HEase (24). The inherent disadvantage of using HEases in genome editing is that most of the HEases studied so far tolerate degenerate sequences, and off-target sites with a few base pair mismatches are also cleaved (25,26). ZF recombinases (ZFRs) have also been constructed by fusion of ZF arrays with Tyr or Ser recombinase for ZFR-mediated integration of the donor plasmid in mammalian genomes and site-specific recombination in a bacterial genome (27,28).…”
Section: Introductionmentioning
confidence: 99%